Greetings from Trinidad, W.I. : Jama masjid, Moslem house of worship - (:unkn) unknown (H.O. Thomas, Trinidad, 2010)
Photo showing mosque in Port of Spain, Trinidad and Tobago. Hand-written letter. 15 cents Trinidad and Tobago stamp.
Colour: White, Green Blue, Red and Cream Hues; Style: Landscape; Other: Unbordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Mosques--Trinidad and Tobago; Churches--Trinidad and Tobago; Islam--Trinidad and Tobago; Muslims--Trinidad and Tobago; Architecture--Trinidad and Tobago